Effects of Brand Love, Personality and Image on Word of Mouth: The Case of Fashion Brand among Young Consumers in Yogyakarta - , HUSEIN YULISAR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is a quantitative study aimed to investigate the effect of brand love, brand personality, and brand image on word of mouth. This research is a replica of previous research conducted by Ismail and Spinelli (2012), "Effects of Brand Love, Personality and Image on Word of Mouth: The Case of Fashion Brands among Young Consumers". The subject in this research is undergraduate student of Universitas Gadjah Mada studying in Yogyakarta who has good knowledge towards apparel fashion brand. The data used in this study is primary data, obtained by distributing online survey based on purposive sampling method to the criteria of the respondents whom aged between 16-23 years old with the total sample 150 respondents. The finding of this research explains that brand personality has positive impact on brand image. Brand personality and brand image have positive impact on brand love. Lastly, brand personality, brand image, and brand love have positive impact on word-of-mouth.